Essential guide towards effective academic writing - Escandor, Danilo E.; Dapat, Rizal O.;Calubayan, Rolando R. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2014)
It is for this reason that this book has been conceptualized - to help you cope with the demand of good academic writing.
Unit 1. Rhetorical principles of writing -- Unit 2. Methods of paragraph development -- Unit 3. Academic research.
Includes bibliographical references and index.
Keywords: ACADEMIC WRITING -- GRAMMAR -- RHETONIC -- COMPOSITION AND EXERCISES